Characterization of millet husk-filled high density polyethylene and polylactic acid composites - Abba, Hammajam A. (2018)
The millet husk fiber (MHF) is an agricultural byproduct from millet (pennisetum glaucum). Currently, the use of thermoplastic composites produced from polymers filled with natural fibers has attracted the attention of many researchers globally. The main objective of this investigation was to study the potential of this agro waste as filler for thermoplastic composites as a substitute to synthetic fibers and other natural fibers. The fibers were treated with sodium hydroxide (NaOH) and pulverized to 250 μm. Fiber loadings of 10 %, 20 % 30 % and 40 % by weight were employed throughout the formulation. Test samples were prepared through melt blend technique followed by compression molding process. The mechanical properties; tensile, flexural and impact test specimens were specified according to ASTM standards and tested using universal testing machine (UTM). The thermal properties were characterized by using thermogravimetric analyzer (TGA).The microstructure observations of fractured surfaces of composites were studied by using scanning electron microscope (SEM).The investigation of water absorption in sea and rain water was determined. The biodegradability was carried out via soil burial technique in municipal and oxisol soils. Tensile strength of untreated fiber millet husk powder (MHP) filled high density polyethylene (HDPE) and MHP filled poly lactic acid (PLA) composites decreased with increased fiber loading but slightly improved for treated fibers composites. While the tensile modulus of both treated and untreated fibers composites increased by increasing the fiber loadings. Flexural strength of the MHP-HDPE treated fiber composites increased as loading increased, while MHP-PLA composites decreased as loading increased. PLA composites exhibit better flexural properties for treated fiber composites. The flexural modulus for both treated and untreated fiber composites of MHP-PLA and MHP-HDPE increased as fiber loadings increases. The impact properties of treated and untreated fibers MHP-HDPE, MHP-PLA, composites drastically decreased as fiber loading increased. Water absorption increased as fiber loading increased. Composites immersed in sea water uptake at higher rate compare to those immersed in rain water. Thermal degradations of untreated and treated fiber composites show slight difference in terms of weight loss, while decomposition rate varies as the fiber loading increased. Biodegradability in municipal soil showed higher rate of degradation compared to oxisol soil. The degradation level for treated and untreated fiber composites differs slightly in both types of soil. MHP-PLA composites degrade faster in both municipal and oxisol soil compare to MHP-HDPE composites. The fiber treatment has little impact on their biodegradability rates. In view of all the findings, it was appropriate to conclude that millet husk fiber filled thermoplastic is a promising composite.